De vita Mosis I: an introduction with text, translation, and notes - Philo, Alexandrinus 25 v.Chr.-40 (Ancient Christianity and Its Contexts Series, 2023)
Cover Page -- Half Title Page, Series Page, Title Page, Copyright -- Contents -- Abbreviations -- Introduction to Philo of Alexandria's De vita Mosis -- Philo of Alexandria -- De vita Mosis I -- On the Life of Moses I -- Bibliography.